On 2D and 3D parameter derivatio n for r ainfall- r unoff models - Martin Adamec; Milan Trizna; Veronika Říhová; Jan Unucka; Marcela Gergeľová (Acta Montanistica Slovaca, 2012)
Geoinformation technology, particularly GIS and digital terrain models, is commonly used at present in order to derive parameters of basins and flow paths. These parameters are subsequently used to create spatially based rainfall-runoff models. In line with the development of geoinformation technologies such models can be derived both in 2D and 3D formats. The question remains whether the 3D format is suitable for all parameters. In order to solve the question two basic parameters that will be affected by the derivation method were selected. One of them, the Subbasin Area parameter, is essential for the calculation of the precipitation volume for a given subbasin area and subsequently for the calculation of the runoff volume. This parameter is directly dependent on the chosen derivation method since the difference in areas derived in 2D and 3D formats depends on the area gradient. The other parameter, River Length, is important for the modelling of water motion within a stream as it influences the shape of hydrograph a nd the size of culmination discharge. Similarly to the first parameter, it is dependent on the area gradient and thus on the used derivation method. A semi-distributed model of the Lubina River basin in the HEC-HMS environment was chosen to represent spatially based rainfall-runoff models. The model was createdon the basis of ZABAGED hypsometry data.Suitability of the use of parameters derived in the 3D formatfor rainfall-runoff modelling is discussed in the concluding partof the paper.